Pembelajaran Konfigurasi Mikrotik Berbasis Model OSI Layer di PT Proxi Jaringan Nusantara - Ivana Lucia Kharisma; Mayang Selpiyana (Lembaga Pengembangan Kinerja Dosen, 2025)
Effective network management is the main need in the world of information technology, especially for companies engaged in network infrastructure. One of the devices that is often used to support network connectivity is MikroTik. This journal aims to design MikroTik configuration learning based on the OSI Layer Model at PT Proxi Jaringan Nusantara, focusing on setting MikroTik so that it can be connected to the internet. The learning method is designed using theoretical and simulation approaches, including the introduction of the OSI Layer Model as the basis of network communication and the technical steps of MikroTik configuration, such as IP Address settings, NAT (Network Address Translation), DHCP Server, and basic Firewall. The simulation results show that the configuration carried out in accordance with the OSI Layer Model can improve network stability and efficiency. This learning is designed to provide practical and in-depth solutions for authors in understanding MicroTik-based network management.